Faktor yang berhubungan dengan Kelelahan Kerja pada Psikososial Karyawan bagian rotary 9 feet di PT Sumber Graha Sejahtera Luwu Tahun 2021 - Lestari S, Andi Dewi; Batara, Andi Surahman; Mutthalib, Nurul Ulfah (An Idea Health Journal, 2021)
Data from the ILO states that almost every year as many as two million workers die due to work accidents caused by fatigue. The study stated that from 58115 samples, 32.8% of them or 18828 samples suffered from fatigue. Surveys in developed countries report that 10-50% of the population experience fatigue. The prevalence of fatigue is about 20% among patients who come in need of health services. The purpose of the study was to determine the psychosocial relationship with the incidence of work burnout at PT Sumber Graha Sejahtera, Luwu Regency in 2021. The type of research was quantitative research using the Cross-Sectional Study method. The research sample was 85 people. The data was taken using a questionnaire and then analyzed using the Chi-square test at a 95% confidence level (?=0.05). The results showed that there was a relationship between psychosocial and work fatigue (? = 0.016).